2010
DOI: 10.1108/02652321011064917
|View full text |Cite
|
Sign up to set email alerts
|

Predicting young consumers' take up of mobile banking services

Abstract: The paper presents theories regarding characteristics of consumer behavior of young customers on the basis of relevant literature and development of electronic banking in the world and in Poland. Aim of this article is to determine attitude of young consumers towards electronic banking based on a survey among group of selected students. This seems especially important because current young consumers are increasingly better educated and are able to determine their needs very precisely. They access information q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
328
12
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(397 citation statements)
references
References 80 publications
43
328
12
14
Order By: Relevance
“…In addition, privacy risk and security risk have been examined in M-banking adoption related studies. This is consistent with extant literature, which has shown privacy risk and security risk to have a strong positive relationship with behavioral intentions (Lee et al 2007;Laukkanen, Cruz 2008;Koenig-Lewis et al 2010;Wessels, Drennan 2010;Negash 2011;Akturan, Tezcan 2012;Chen 2013).…”
Section: Discussion and Limitationssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, privacy risk and security risk have been examined in M-banking adoption related studies. This is consistent with extant literature, which has shown privacy risk and security risk to have a strong positive relationship with behavioral intentions (Lee et al 2007;Laukkanen, Cruz 2008;Koenig-Lewis et al 2010;Wessels, Drennan 2010;Negash 2011;Akturan, Tezcan 2012;Chen 2013).…”
Section: Discussion and Limitationssupporting
confidence: 81%
“…Adoption factors Luarn and Lin (2005) usefulness, convenience, credibility, self-efficacy, cost Laukkanen (2007) efficiency, convenience, safety Lee et al (2007) perceived risk, perceived usefulness, trust Laukkanen and Cruz (2008) usage, value, risk, tradition and image Kim et al (2009) relative benefits, trust, structural assurances Gu et al (2009) usefulness, convenience, trust Crabbe et al (2009) perceived credibility, facilitating conditions Püschel et al (2010) compatibility, convenience, relative benefit, visibility, demonstrability, image, triability, perceived behavioral control, facilitation condition, subjective norm, testability, intention Koenig-Lewis et al (2010) compatibility, perceived usefulness, risk, trust, cost Cruz et al (2010) cost, risk, perceived advantage, complexity Wessels and Drennan (2010) usefulness, risk, convenience, financial cost, compatibility Zhou et al (2010) task characteristics, technology characteristics, convenience conditions, task technology fit, performance expectancy, effort expectancy, social influence Riquelme and Rios (2010) intention, perceived relative advantage, perceived risk, social norms, convenience, usefulness Singh et al (2010) usefulness, ease of use, subjective norms, self-efficacy, cost, safety, trust Lin (2011) perceived advantage, ease of use, compatibility, competence, benevolence, integrity Negash (2011) usefulness, convenience, enjoyment, network quality, security, privacy, trust, awareness, regulation, compliance Akturan and Tezcan (2012) risk, ease of use, usefulness, benefit Zhou (2012) structural assurance, ubiquity, ease of use, personal innovativeness Chen (2013) advantage, concurrency, trialability, complexity, different risk types, attitude, intention to use, brand image, brand awareness Hanafizadeh et al (2014) usefulness, ease of use, the need for interaction, risk, cost, compatibility with life style, credibility, trust Bidar et al (2014) usefulness, ease of use, security, privacy, compatibility, social influence, facilitating conditions, cost…”
Section: Authorsmentioning
confidence: 99%
“…Perceived usefulness, perceived ease of use, perceived risk, attitude → adoption intention Consequent to the development, adoption and usage of various IS over the last two decades, the scope of PU and PEOU has been extended and tested as key independent variables and intention drivers in various settings, including the context of developing countries. The literature has examined the intention to adopt m-banking services (Chitungo and Munongo, 2013), ATT towards using electronic learning acceptance (Cheng, 2011), behavioral intention to use m-services (Wang et al, 2006), intention to adopt email authentication services (Herath et al, 2014), intention to use online banking (Lee, 2009), and behavioral intention to adopt m-banking services (Koenig-Lewis et al, 2010), among other factors.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Their results also revealed that Internet banking, ATM, and phone banking substituted each other and Internet banking was considered to be efficient for ease of use and access, and that the users of Internet banking lack confidence in the security of the web sites of Internet banking. Koenig-Lewis et al (2010) studied the barriers for enhancing mobile banking services by looking into two widely used models for technology adoption: the Technology Acceptance Model (TAM) and Innovation Diffusion Theory (Dillon & Morris, 1996;Venkatesh et al, 2003). They studied a model to forecast consumers' intention to apply mobile banking.…”
Section: Introductionmentioning
confidence: 99%